The Design of a Smart Refrigerator Prototype - Z Ali; S. E. Esmaeili (IAES Indonesia Section, 2017)
The technological development nowadays has enabled the use of smart appliances and machines almost everywhere. The refrigerator is considered one of the most important appliances that is being used in almost every place for the purpose of storing foods, drinks, and medicines at cold temperatures, and in a sealed place to avoid exposure. However, there are several challenges encountered with refrigerators; like the expiration of some of the items inside the fridge, the need to know the exact count and availability of the items, potential liquid leaks, and open fridge door. A smart refrigerator is proposed as a solution to the aforementioned problems. The proposed smart refrigerator uses a Radio Frequency Identification (RFID) reader, the Arduino Uno microcontroller, RFID tags for all items in the fridge, a user friendly application developed using Microsoft Visual Studio, MySQL main database developed by the suppliers to store the information related to each purchased item and Phidget Interface Kit board.